A study on the potential of polystyrene lightweight aggregate in concrete - Fetra, Venny Riza (Universiti Malaysia Perlis, 2010)
Economic reason caused the used of expandable polystyrene increasing every year. The consequence is that the polystyrene wastes also mounted day by day. On the other hand, the source of natural aggregate is non-renewable. Public awareness to save the environment is always be campaigned through all kind media to reuse, reduce or recycle. This research comprised the effort to produce lightweight aggregate concrete from waste expandable polystyrene or also known as polystyrene foam that can be found easily around our neighborhoods as electronic packaging. The polystyrene lightweight aggregate was produce on reducing the size into several mm and prior to heat treatment at temperature ranging from 130°C to 180°C. Characterization of this polystyrene lightweight aggregate were done by several experiments that includes shrinkage measurements, bulk density, water absorption level, compressive strength, also utilized the observation of light microscope, scanning electron microscope, even just visual observation by human eye. In this work, the polystyrene lightweight aggregate product was incorporated in concrete. Concrete characterization was conducted similar to those for aggregate with additional the slump test, compression test and flexural test. The results showed that the best temperature to produce aggregate with highest compressive strength 69.2 MPa was 170°C where the water absorption levels only 2.4% and its bulk density 154.6 kg/m3. This result of bulk density satisfied the classification of lightweight aggregate concrete according to ASTM C330. Unfortunately, this lightweight aggregate concrete compressive strength only 9.8 MPa was not reached the requirements strength for structural concrete which is 17 MPa for 28-day compressive strength. Thus, the used of this polystyrene lightweight aggregate concrete limited for non structural purpose only.